Testing allopatry and ecological speciation hypothesis in the roundleaf bats (family: hipposideridae) through genetics, morphometrics, and echolocation datasets - Sultana Habeebur; F.A.A. Khan; A.R. Mohd Ridwan; Jayaraj V.K; S. Badiozaman; M.T. Abdullah (2016)
To date, there are very few attempts to describe geographically distinct evolutionary lineages within Malaysian roundleaf bats (Genus Hipposideros).Use of different marker may also result in an underestimation in an actual bat diversity. Our study aimed to evaluate the taxonomy of Hipposideros galeritus using genetics, morphometrics, and echolocation datasets. Previous molecular studies showed that H. galeritus was paraphyletic with H. cervinus and within the currently recognized H. galeritus lineages, high intra-specific divergence were observed. Our morphometric analyses based on 35 skull measurements from Borneo and Peninsular Malaysia indicate that the distance between the cochleae and second molar tooth crown length are the best resolving characters, but no statistically significant clusters were formed to discriminate the assigned groups. Similarly, our phylogenetic analyses revealed deep genetic divergence between populations sampled from different geographical area (3.0-15.0% for concatenated genes of cytochrome-b and cytochrome oxidase-I genes). Echolocationcall analysis suggests that H. galeritus from several localities in northen and southern Sarawak exhibit a range of call frequencies from 100-115 kHz, contrasting to the Peninsular Malaysia (Penang and Kelantan) samples which had a call frequencies ranging from 90-95 kHz. The combination of genetic, morphometrics, and echolocation data from this study provide support to elevate subspecies H. galeritus labuanensis to specific rank (H. labuanensis). Additionaly, our data also suggest that population from Southwestern Borneo may represent a several species from those in Sabah. Our finding emphasise the importance of multiuple datasets in understanding how past biogoegraphic event had shaped species diversity in Southeast Asia.